2016
DOI: 10.1177/0954008316665678
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermal and mechanical properties of polymer nanocomposites based on organosoluble polyimide with naphthyl pendent group and layered double hydroxide

Abstract: In this study, a soluble aromatic polyimide (PI) with naphthyl pendent group was initially synthesized by the reaction of pyromellitic dianhydride (PMDA) with 5-methyl- N,N-bis(4-nitrophenyl)naphthalen-1-amine. Then, via co-precipitation reaction of zinc nitrate hexahydrate and chromium nitrate nonahydrate, Zn/Cr-layered double hydroxide (LDH) was synthesized using hydrothermal techniques. Finally, different novel nanocomposites (NCs) based on PI and Zn/Cr-LDH (1, 2, 4 wt%) were produced through in situ polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is also expected that the efficient design of PIs and their nanocomposites will be highly critical in the delivery of excellent performance at reasonable cost. 31,32 In this study, we have demonstrated that diamine containing naphthalene and 1,2,3-triazole could be successfully synthesized, initiated with the click reaction, and used to prepare aromatic PI nanocomposites with ZnO. The transparency, thermal stability, and mechanical properties of these PI/ZnO nanocomposite films were addressed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is also expected that the efficient design of PIs and their nanocomposites will be highly critical in the delivery of excellent performance at reasonable cost. 31,32 In this study, we have demonstrated that diamine containing naphthalene and 1,2,3-triazole could be successfully synthesized, initiated with the click reaction, and used to prepare aromatic PI nanocomposites with ZnO. The transparency, thermal stability, and mechanical properties of these PI/ZnO nanocomposite films were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…It is also expected that the efficient design of PIs and their nanocomposites will be highly critical in the delivery of excellent performance at reasonable cost. 31,32…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are several ways to increase pores in the film: (1) Add unstable components to the polyimide matrix, and then decompose at high temperature to produce pores 16-18 ; (2) add pore-containing fillers to the polyimide matrix 7,19-23 ; (3) link bulky substituents on the side chain of polyimide or increase the free volume fraction by changing the tightness of polyimide molecular chains through branched cross-linking. [24][25][26][27] In addition, adding nanomaterials to the polyimide matrix can not only improve the mechanical properties and thermal properties [28][29][30][31][32] of the material, but also reduce the dielectric constant of the material. In summary, adding a filler containing a porous structure to the polyimide matrix for the purpose of reducing dielectric constant is the simplest and most commonly used method.…”
Section: Introductionmentioning
confidence: 99%
“…6 Among nanofillers, the layered double hydroxides (LDHs) are one of the most specific inorganic fillers that have been used extensively in polymer nanocomposite preparation. [7][8][9][10][11][12][13] The growth of LDH nanocomposites has increased in recent years. LDHs have been reported to significantly improve the mechanical and thermal properties of the end-use polymer products.…”
Section: Introductionmentioning
confidence: 99%
“…6 Among nanofillers, the layered double hydroxides (LDHs) are one of the most specific inorganic fillers that have been used extensively in polymer nanocomposite preparation. 713…”
Section: Introductionmentioning
confidence: 99%